A New Hybrid Dual Active Bridge Modular Multilevel Based DC–DC Converter for HVDC Networks - Mohamed Ashraf; Yousef Nazih; Fahad Alsokhiry; Khaled H. Ahmed; Ayman S. Abdel-Khalik; Yusuf Al-Turki (IEEE Access)
Multi-terminal high voltage DC transmission currently represents a leading technology in long-distance power transmission systems. Among the main technical challenges facing such technology, DC fault isolation, permitting different grounding schemes, providing interoperability, and high DC voltage stepping between different HVDC networks, and allowing high-speed power reversal without power interruption especially when connecting the pre-existing voltage source converters (VSC) and line commutated converters (LCC)-based HVDC networks. This paper introduces a new modular multilevel converter (MMC) based front-to-front DC-DC converter to interconnect two different types (LCC/VSC) of HVDC networks. The proposed topology comprises a voltage source MMC (VS-MMC) and a current source MMC (CS-MMC), while both are coupled via an AC link including the isolating transformer. The proposed topology can successfully provide an uninterruptible bi-directional power flow, high DC voltage stepping with a DC fault blocking capability, and low number of semiconductors due to the usage of only half-bridge SMs. The system design is provided with a detailed mathematical analysis. Furthermore, two active power control methodologies are proposed and compared. The first control technique is simpler and entails lower passive elements, while the second technique ensures a zero reactive power over the full range of active power flow. Furthermore, Losses analysis and comparison are provided between the two proposed control techniques. Finally, Control-Hardware-in-the-Loop (CHiL) test validation is employed to confirm the validity of the proposed system under healthy as well as different fault scenarios.